Pengaruh Pemberian Pupuk Hayati Azotobacter dan Pupuk Kandang Sapi Terhadap Pertumbuhan dan Produksi Tanaman Sawi (Brassica Juncea L.) - Tamba, Handika (LPPM Universitas Katolik Santo Thomas Medan, 2025)
This research was conducted in Selayang Village, Selesai District, Langkat Regency, North Sumatra Province. Starting in May until July 2024. The purpose of this study was to determine the effect of Azotobacter and cow manure on the growth and production of mustard greens. This study used a Factorial Randomized Block Design (RAK) with 2 treatment factors. The first factor is Azotobacter with the symbol (A) which consists of 2 treatment levels, namely: A1 = 15 ml / Liter of water, A2 = 30 ml / Liter of water. The second factor is Cow Manure (K) which consists of 3 treatment levels, namely: K0 = 0 grams / polybag, K1 = 75 grams / polybag, and K2 = 150 grams / polybag. The parameters observed in this study were plant height (cm), number of leaves (strands), leaf area (cm2), plant wet weight (grams), and plant root wet weight (grams). Azotobacter treatment significantly affected the parameters of leaf area, plant wet weight, and root wet weight. The best treatment was treatment A2 (30 ml/L). Cow manure treatment significantly affected the parameters of plant wet weight and root wet weight. The best treatment was treatment K2 (150 grams/polybag). The interaction of Azotobacter and cow manure treatments significantly affected the parameters of plant height at 4 MST, number of leaves at 4 MST, leaf area, and plant wet weight. The best treatment was the A2K0 treatment (Azotobacter 30 ml/L and cow manure 0 grams/polybag).